Realizing Ecocooperation Transformation through Eco Enzyme: Turning Waste into Benefit - Thamara Putriani Br Matanari; Nurus Shalihin; Walan Yudhiani (Yayasan Keluarga Guru Mandiri, 2025)
This study focuses on enhancing agricultural productivity through sustainable resource management, community empowerment, and local innovation in the form of eco enzyme production by the Sumber Rezeki Women Farmers' Group (KWT). Conventional farming practices and a lack of innovation often hinder productivity. This research aims to increase productivity and community self-reliance by transforming organic waste into eco enzyme, aligning with global trends in social group strengthening and sustainable agriculture innovation. Using the Community-Based Research (CBR) approach, the study followed four stages: foundation, planning, data collection and analysis, and action. Data were gathered through observation, interviews, documentation, and focus group discussions, and analyzed using the Miles and Huberman model. The results revealed three key findings: 1) mentoring in eco enzyme production improved members' skills and knowledge; 2) the program's success was supported by sustainability commitment, local wisdom-based solidarity, and innovation-driven self-reliance; 3) the cooperation of these elements forms the concept of Ecocooperation Transformation, which enhances productivity while strengthening community resilience. This study contributes to the literature on local innovation and community empowerment in sustainable agriculture and offers a replicable model of Ecocooperation Transformation for other communities. In conclusion, collaboration, local innovation, and community strengthening are essential to achieving sustainable agricultural productivity and self-sufficiency.